Monitoring the complexity of ventricular response in atrial fibrillation - H. Käsmacher; S. Wiese; M. Lahl (Discrete Dynamics in Nature and Society)
Atrial fibrillation does not present a uniform extent of variability of the ventricular response exemplifying periodicities and more complex fluctuations, due to varying number and shape of atrial wavelets and aberrant conduction in the AV-junction. It was sought to categorise different degrees of complexity introducing an uncomplicated monitoring method for that objective.